Acute hemolytic anemia with rare etiology - Gupta, Saumya; Nahid, Eram; Meena, L P (Indian Journal of Case Reports, 2019)
Naphthalene is a widely used industrial and household chemical in the form of mothballs. But it has rarely been used as an agent of poisoning worldwide. Here, we describe the case of acute hemolytic anemia with methemoglobinemia following ingestion of naphthalene mothballs. A 26-year-old female ingested 6 mothballs and presented three days later with hemolysis and methemoglobinaemia. She was given intravenous methylene blue, N-acetylcysteine and ascorbic acid, besides supportive treatment. Renal replacement therapy in the form of hemodialysis was done on an alternate day basis. She was discharged after ten days on outpatient follow-up.